Pengaruh Perputaran Modal Kerja Dan Likuiditas Terhadap Profitabilitas (Studi Kasus Pada Sub Sektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia Periode 2014-2018) - Rahmaita (CV. ITTC INDONESIA, 2023)
The purpose of this study was to determine whether working capital turnover has an effect on profitability in the food and beverage sector listed on the Indonesia Stock Exchange for the 2014-2018 period. . The objects of research in this study are Food and Beverage Companies listed on the Indonesia Stock Exchange for the 2014-2018 period. Based on the partial hypothesis test (t test) it shows that the working capital turnover variable has an effect and is significant on ROA.